PENGARUH POLA SOSIALISASI, PERSEPSI PELANGGAN DAN CITRA PERUSAHAAN TERHADAP CITRA PRODUK DAN KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK LISTRIK PINTAR (PRABAYAR) DI PT. PLN (PERSERO) AREA KOTA PEKANBARU - Andrian, Nico; Zulkarnain, Zulkarnain; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2018)
The research held in PT. PLN (persero) Area Kota PekanbaruCustomer. This research held in order to analyze the direct and indirect impact ofpatterns socialization, customer perceptions, and corporate image on productimage and customer buying decision in product smart electrical (prepay). Thepopulation is consist of 14.955 customer smart electrical (prepay) in PT. PLN(persero) Area Kota Pekanbaru. According to the sample in formula slovin thenumber of research sample is drawn to 100 people. The variabel used arepatterns socialization, customer perceptions, and corporate image as dependenvariable, variable product image as intervening variable and variable customerbuying decision as independen variable. Analytical tool used is descripitiveanalysis and Structural Equation Modeling (SEM) using SmartPLS 2 tool. Thestatistical test shows that corporate image influence customer buying decision,product image influence customer buying decision. Patterns socializationindirectly influence customer buying decision through product image, andcustomer perceptions indirectly influence customer buying decision throughproduct image. This research recommended to company must be able to developand maintain product image, well as maintain and increase patterns ofsocialization and customer perceptions already well provide accurateinformation, as well enhance the corporate image with increase fasilitas andother support.